Treatment of Periodontal diseases by local delivery system - F. Haghighati; R. Safaie (Tehran University of Medical Sciences, 1995)
According to the role of microbes as etiologic factors of periodontal diseases, mechanical factors are required to eliminate microbial plaque. Although systemic chemotherapy is mentioned in the articles, it is still ineffective on adult periodontitis. Therefore, using local antibacterials and controlling their release have been considered. In this article, methods and materials that can result in antibacterial slow release in local delivery systems are discussed.